1972
DOI: 10.1017/s0022172400022476
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of cross-protection afforded by dengue virus against West Nile virus in hamsters

Abstract: SUMMARYThe protection afforded by similar concentrations of different dengue virus serotypes against a subsequent challenge of West Nile virus was studied in hamsters. The New Guinea C strain of dengue 2 virus gave the best protection. It was found that the anamnestic neutralizing antibody response induced by the challenge West Nile virus against West Nile virus in hamsters, previously immunized with dengue 2 virus, might play a major role in the cross-protection observed in this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…Studies from several decades ago showed that polyclonal sera directed against the E protein can protect against lethal flavivirus challenge in animals (6,41). More recent experiments with WNV, DENV-1, and DENV-2 (4,15,16,37,46,49,53) have suggested that DIII of the E protein is a key target for strongly neutralizing MAbs, although the human B cell repertoire may be directed away from this region (38,55,59).…”
Section: Generation Of Mabsmentioning
confidence: 99%
“…Studies from several decades ago showed that polyclonal sera directed against the E protein can protect against lethal flavivirus challenge in animals (6,41). More recent experiments with WNV, DENV-1, and DENV-2 (4,15,16,37,46,49,53) have suggested that DIII of the E protein is a key target for strongly neutralizing MAbs, although the human B cell repertoire may be directed away from this region (38,55,59).…”
Section: Generation Of Mabsmentioning
confidence: 99%
“…Enhanced infection after transfer of either pooled human cord blood from DENV-immune mothers (Halstead, 1979) or a chimeric human-chimpanzee anti-DENV neutralizing monoclonal antibody (mAb) (Goncalvez et al, 2007) resulted in increased viremia in rhesus monkeys that is postulated to represent antibody-dependent enhancement (ADE). In mice, protection from death using a secondary, homologous (serotype-specific) DENV infection has been demonstrated (Johnson and Roehrig, 1999; Price and Thind, 1972); while reports of heterologous sequential DENV infections in mice noted an increase in thrombocytopenia (Sarkar et al, 1976) or documented heterologous immune responses (Beaumier et al, 2008). To the best of our knowledge, no published study in mice has documented the occurrence of either protection or enhancement of DENV titers in sequential, heterologous infections.…”
Section: Introductionmentioning
confidence: 99%
“…WNV infection has been studied in several animal models, including chickens, geese, rat, mice, hamsters, and monkeys (4,9,17,31,41,48). However, the pathophysiology of invasiveness of WNV into the CNS, the mechanism of neurodegeneration, and the immune response after infection are still poorly understood.…”
mentioning
confidence: 99%